Dermatite atópica na infância e a marcha atópica. - Borges, João Vitor da Silva (2024)
Atopic Dermatitis (AD) is a chronic, multifactorial inflammatory skin condition, predominantly affecting children up to the age of seven. Two primary theories currently explain its pathophysiology: the "outside-in theory" and the "inside-out theory." The "outside-in theory" posits that mutations in the Filaggrin (FLG) gene, essential for skin formation and the regulation of IgE synthesis via cytokines IL-4, IL-5, and IL-13, play a critical role. In contrast, the "inside-out theory" suggests that AD arises from the intense itching experienced by patients. Despite these theories, the pathogenesis of AD remains incompletely understood. Moreover, recent research has identified a complex array of AD endotypes, characterized by at least four distinct biomarker clusters, which will be discussed in detail throughout this review. Additionally, AD is often the initial manifestation of a broader atopic phenotype in childhood, potentially leading to other atopic conditions such as allergic asthma, allergic rhinitis, and food allergies, collectively known as the "atopic march." Therefore, the objective of this review is to enhance the understanding of AD pathophysiology in childhood and its relation to the development of the atopic march.